The design of ultra wideband six-port network by using ground-slotted technique - Yusof, Khairul Huda (2014)
A new design of compact ultra wideband (UWB) six-port network by using ground-slotted technique is presented in this paper. The proposed six-port network is accomplished by constructing four in-phase two-section power dividers and two 90o power dividers by using CST Microwave Studio 2010. The presented result shows that the proposed UWB six-port network offers good amplitude and phase characteristic performances for frequency range of 3.1 to 10.6 GHz. © 2014 Warsaw University of Technology (WUT).